The Scope of Statutory Protection on the Use of Identical or Confusingly Similar Names by Businesses in Bangladesh - Zaman, Shima (Dhaka University Law Journal, 2021)
Abstract not available Dhaka University Law Journal, Vol. 31, 2020 P.49-62